PEDIATRIC NEUROMUSCULAR INTERVENTION TO INCREASE MOTORIK IN AGNESIS CORPUS CALLOSUM ETCAUSA CEREBRAL PALSY - Safitri, Amaliyah Hana; Susilo, Taufik Eko (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Describe clinical reports of pre- and postneurofunctional interventions in cases of agenesis of the corpus callosum. Clinical case: The baby was born spontaneously with a weight of 3100 g, 40 weeks of gestation and required a stimulus of applause for 10s until finally the baby cried for the first time. The baby was born with the thumb congenitally entwined bilaterally. At the initial evaluation, the child has fluctuating tone in the upper and lower extremities. Spasm in the upper trapezius, tibialis anterior and facial muscles (frontal, masseter, obricularis oris), very weak central muscles and hypotonia of the upper and lower extremities. The goals of neurofunctional intervention are to improve motor skills, improve head control, improve core ability in sitting position, and readiness to crawl. the child did not show any orthopedic deformities, but there was limited range of motion and muscle weakness and changes. Conclusion: Functional focused motor interventions proved to be effective, as GMFM showed an improvement in gross motor function after a short intervention period from 31 points to 48 points in the total dimension B.